P01.060 PriCoTTF: a phase I/II trial of Tumor Treating Fields prior and concomitant to radiotherapy in newly diagnosed glioblastoma. (19th September 2018) - Glas, M; Scheffler, B; Lazaridis, L; Herrlinger, U; Pierscianek, D; Sure, U; Pröscholdt, M; Hau, P; Hense, J; Kleinschnitz, C; Grosu, A; Stuschke, M; et al.
Abstract: Objective: Tumor Treating Fields (TTFields) in combination with adjuvant temozolomide (TMZ) as therapy for newly diagnosed glioblastoma (GBM) patients showed significantly increased progression-free survival (PFS), overall survival (OS) and long-term survival rates in the EF-14 phase III trial. In the trial, patients were randomized after completion of radiochemotherapy, and TTFields therapy was initiated in combination with adjuvant chemotherapy. In preclinical settings, TTFields synergistically enhanced efficacy of radiotherapy in GBM, hypothetically by inhibiting DNA damage repair in irradiated cells. The presented phase I/II trial will evaluate safety and feasibilty of TTFields initiated prior and concomitant to combined radiochemotherapy in newly diagnosed GBM. Methods: In arm A of this prospective multi-center trial, seven eligible patients with newly diagnosed GBM will be enrolled initially. Provided that treatment is tolerated well, enrollment will continue for up to 20 patients. Patients will be subjected to TTFields after complete wound-healing following surgery. TTFields treatment will be continued throughout radiochemotherapy and adjuvant chemotherapy for six cycles. In total, patients will receive TTFields therapy for approximately nine months. In arm B, elderly patients with a reduced KPS (50 or 60) will be treated with postsurgical TTFields therapy followed by TTFields therapy concomitant to hypofractionated radiotherapy with 40 Gy for three weeks. In line with arm A, TTFields therapy will continue beyond radiotherapy throughout adjuvant chemotherapy for a total of nine months. In the first stage, six patients will be accrued. Under the provision of an acceptable safety profile, seven additional patients will be accrued for a total of thirteen patients. Results: The primary endpoint of the trial is safety and tolerance based on the frequency of a set of predefined treatment-limiting toxicities (TLTs). Secondary endpoints consist in particular of PFS, OS, radiologic response and frequency of adverse events. First experiences will be presented. Conclusion: The objective of this trial is to demonstrate that the administration of TTFields therapy prior and concomitant to radiotherapy and adjuvant chemotherapy is feasible and safe. Moreover, first data obtained on efficacy may serve as a basis for a potential randomized phase III trial.